Single Cell Sequencing, Its Application and Future Challenges - Saleem, Misbah; Alam, Sadaf; Kainat, Iqra; Iftikhar, Ramsha; Ijaz, Aqsa (Current Trends in OMICS, 2021)
Single-cell sequencing investigates the differences in proteomic and genetic information about individual cells by using next-generation sequencing technologies. Sequencing of the whole genome, epigenome, and transcriptome involves the heterogeneous process of diagnosis, progression, and treatment of disease. Previous studies show that only a few selected proteins and RNAs can be measured but recent molecular studies explore that advances in next-generation sequencing and whole genome amplification enabled us to examine the differences among a variety of transcriptomic cells, gene expression, and phenotypic expressions. In our study, we try to summarize different technologies and their applications at single-cell level in diverse fields such as embryology, oncology, immunology, neurology, microbiology, tissue and organ development, antibody screening, and stem cell research.